Investigating environmental impacts of betel nut (Areca chatechu) waste disposal based on human behavior in Port Moresby, Papua New Guinea - Pendis Ono; M Maryono; Fuad Muhamad (Diponegoro University, 2023)
The consumption of Areca catechu (betel nut) in combination with Piper betel and lime (calcium hydroxide) in Papua New Guinea has been a daily consumable commodity among the country’s population. Due to the increase usage of betel nut, more wastes tend to be deposited into the city’s environment making the city very filthy. The disposal of wastes along with its end byproducts has become a major problem for the environment due to uncontrolled human behavior and ignorance. The city of Port Moresby has seen a lot of wastes from betel nut husks and salivary spittle being spewed all over public places. The uncontrolled wastes disposal and carelessness of the people has significantly affected the outlook of the surrounding environment. Even though, laws were put in place to manage wastes, people do not care of the impacts and continue to ignore the laws. The study was undertaken to understand human behavior and characteristics towards improper waste management and determine the level of wastes derived from the use of betel nut. The study was conducted using simple random sampling and stratified sampling methods through interviews for qualitative data collection. The results revealed that ignorance and carelessness exist within the population in managing betel nut wastes. The results also indicate that banning the sale and trading of betel nut may lead to social and economic problems for most of the unemployed population in Port Moresby. Therefore, it requires a better approach from the government and the city authorities to develop and implement workable win-win solution to the problems faced by the city residence as well as managing their wastes from the use of betel nut.